Improving Textile Production Efficiency Through the Implementation of Lean Manufacturing in the Weaving Department (Journal of Renewable Engineering, 2026)
This study examines how a customized Lean Manufacturing approach can improve production efficiency in the weaving department of a textile company. Weaving operations frequently experience inefficiencies due to machine downtime, waiting time, excessive operator movement, and product defects, which create a gap between targeted and actual output. A quantitative case study design was applied using direct observation, time study, Value Stream Mapping, production records, and maintenance logs. Lean tools including 5S, Total Productive Maintenance, layout improvement, line balancing, poka yoke, and Kaizen were implemented in a pilot weaving area. The results indicate a significant reduction in machine downtime by 53 percent, waiting time by 59 percent, operator movement by 39 percent, and defect rate by 50 percent. Value Stream Mapping analysis further shows that non value added time decreased substantially while value added time remained stable, leading to a 24 percent reduction in total lead time and a 22 percent increase in daily production output. These findings confirm that Lean Manufacturing, when customized to the characteristics of weaving processes, effectively eliminates waste and enhances workflow. The study concludes that integrating Lean with maintenance and process standardization provides a practical strategy to bridge the gap between production targets and actual performance in textile weaving units.